2020
DOI: 10.2174/1871530319666191202115149
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Regulates CCL5 and PPARγ Expression in Nthy-ori 3-1 Cells: Possible Involvement of Caveolin-1 and CCL5 in the Pathogenesis of Hashimoto’s Thyroiditis

Abstract: Background: Hashimoto’s thyroiditis (HT) is characterized by lymphocytic infiltration of the thyroid parenchyma, which ultimately leads to tissue destruction and loss of function. Caveolin-1 (Cav-1) is an essential structural constituent of lipid rafts in the plasma membrane of cells and is reported to be significantly reduced in thyrocytes from HT patients. However, the mechanism of Cav-1 involvement in HT pathogenesis is still largely unclear. Methods: Cav-1 expression in thyroid tissues from HT patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition, in prostate cancer, CAV1 affects lymphangiogenesis mediated by the panangiogenic factor vascular endothelial growth factor A (VEGFA) [ 32 ]. CAV1 inhibition results in the upregulation of CCL5 expression in human thyroid follicular epithelial cells [ 33 ]. In our study, the increase in Vegfa levels was greater in the injury group than in the sham group (1.43-fold change, p = 0.0484).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in prostate cancer, CAV1 affects lymphangiogenesis mediated by the panangiogenic factor vascular endothelial growth factor A (VEGFA) [ 32 ]. CAV1 inhibition results in the upregulation of CCL5 expression in human thyroid follicular epithelial cells [ 33 ]. In our study, the increase in Vegfa levels was greater in the injury group than in the sham group (1.43-fold change, p = 0.0484).…”
Section: Discussionmentioning
confidence: 99%
“…The TSH-lowering effect of selenium supplementation is unlikely to be related to changes in humoral markers of autoimmunity and/or circulating CXCL9 [ 43 ]. In vitro experiments showed that the expressions of CCL5 and migration of peripheral blood mononuclear cells were markedly increased, while the level of PPARγ was significantly decreased after the lentivirus-mediated knockdown of Cav-1 in Nthy-ori 3–1 cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…which reduces the intrinsic antiviral response, stimulates the recruitment of inflammatory lymphocytes, and promotes inflammatory changes [17]. Numerous studies have demonstrated a positive correlation between increased CCL5 expression with inflammatory infiltration in HT patients [18][19][20] and pulmonary fibrosis patients [21].CD68 expression was increased in patients with HT [22] and IPF [23], which may be related to immune processes. An association between the increased CD68positive cells and the increased percentage of lung tissue in IPF patients was found [24].…”
Section: Discussionmentioning
confidence: 99%